Traditional gender inequalities limit pastoral women’s opportunities for adaptation to climate change: Evidence from the Afar pastoralists of Ethiopia - Selam Balehey; Girmay Tesfay; Mulubrhan Balehegn (Pastoralism, 2018)
Abstract Climate change affects different demographic groups differently. Pastoral women, being among the poorest of the poor, are expected to be highly vulnerable to climate change. However, empirical evidence on gender-differentiated vulnerability and adaptive capacity is limited. A triangulation of different techniques including focused group discussions, individual interviews, case studies and structured observations was used to see if there is a difference in factors that determine the level of vulnerability and adaptive capacity between Afar men and women. Gender inequality inherent in the Afar customary tradition (Adda) acts as a risk multiplying factor, resulting in women being more vulnerable than men to climate change-induced food insecurity and related risks. Moreover, men have better scores in different variables determining vulnerability and adaptive capacity, including wealth ownership, wealth inheritance, household-level decision power, opportunities for community-level participation, household burdens and health or body mass index (BMI). Despite their limited scores in many of these factors, Afar pastoral women make higher contributions to household-level adaptation to recurrent drought and weather variability. A gendered approach that recognizes the difference in potentials, limitations and vulnerabilities of pastoral women and men is required for successful implementation of adaptation measures.